2013
DOI: 10.1542/peds.2012-3640
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery for Severe Obesity in Two Adolescents With Type 1 Diabetes

Abstract: Bariatric surgery has been effective in treating type 2 diabetes mellitus (T2DM); it has not been used frequently in obese patients with type 1 diabetes mellitus (T1DM). This is the first case series reporting on the effect of bariatric surgery on diabetes control in adolescents with T1DM. Patient A is a 19-year-old obese man with T1DM who underwent vertical sleeve gastrectomy. At 12 months after surgery he demonstrated 28% reduction in BMI. His daily total insulin requirement had decreased; however, hemoglobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
1
28
1
1
Order By: Relevance
“…Most evidence to support BS in T1DM is derived from small case series or case reports (Table 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The data are also limited by a number of factors: heterogeneous data, short follow-up periods and inclusion of different types of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most evidence to support BS in T1DM is derived from small case series or case reports (Table 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The data are also limited by a number of factors: heterogeneous data, short follow-up periods and inclusion of different types of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, nonobese T1DM patients have an increased risk of obesity due to the anabolic effects of insulin and due to their frequent use of simple sugars for hypoglycemic episodes [6]. However, the medical literature which describes BS in T1DM patients is limited to few case series and scattered case reports, with conflicting results (Table 1) [7][8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 99%
“…In one comparative series, remission rates of hypertension and dyslipidemia were similar among patients with T1D and T2D after bariatric surgery (31). A few studies also reported evidence of improvement in sleep apnea (31,43), kidney function and microalbuminuria (30,33,38,39,45), retinopathy (33), and quality of life (38,41,43) after surgery. A reduction in the number and dosage of medications needed to treat diabetes, hypertension, dyslipidemia, and other obesity-related comorbidities following bariatric surgery would be an additional benefit (22)(23)(24)27,32).…”
Section: Impacts On Obesity and Diabetes Comorbiditiesmentioning
confidence: 92%
“…Such beneficial effects on obesity-related comorbidities can also be extrapolated to severely obese patients with T1D. Improvement in lipid profile (30)(31)(32)(33)38,39,(41)(42)(43)(44) and blood pressure (30,31,38,39,41,45) was shown in some studies. In one comparative series, remission rates of hypertension and dyslipidemia were similar among patients with T1D and T2D after bariatric surgery (31).…”
Section: Impacts On Obesity and Diabetes Comorbiditiesmentioning
confidence: 97%
See 1 more Smart Citation